PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS SMAN 11 PEKANBARU - Fitri Ayu Ningtiyas; Putri Yuanita; Armis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is a class action research that aims to improve the learning process and to increase the student’s mathematics learning outcomes by applying cooperative learning Think Pair Square (TPS) approach. The subjects of this research are the student of class X2 SMAN 11 Pekanbaru at second semester of academic years 2014/2015, which amounts to 34 students. This research consists of two cycles, each cycle consists of four stages: planning, implementation, observation, and reflection. Data collected through observation and learning outcomes test. Data analysis is done by observation data analysis and student’s mathematics learning outcomes data analysis. The action is successful if teacher’s activities and student’s activities increase in every meeting and the number of students who reach Minimum Mastery Criteria increases in every cycle. Results of research on the observation sheet shows the activity of teachers and students have executed better and has improved at each meeting. Percentage students that reach knowledge Minimum Mastery Criteria in base score is 8,82% increase to 41,18% at the first cycle and 73,53% at the second cycle. The result of this research showed that cooperative learning Think Pair Square approach improve the learning process and increase the mathematics learning outcomes the students of class X2 SMAN 11 Pekanbaru at second semester of academic years 2014/2015. Keywords: Mathematic learning outcomes, Think Pair Square, Class action research